STRATEGI PENGEMBANGAN UMKM DESTINASI PARIWISATA SUPER PRIORITAS LABUAN BAJO DALAM MENINGKATKAN DAYA SAING DAN KEBERLANJUTAN EKONOMI LOKAL - Adamy, Zulham; Wiradharma, Gunawan; Aditya Prasetyo, Mario; Paulina Soko, Imelda; Igiriza, Miftahunnisa’ (Penerbit Lafadz Jaya, 2025)
This research investigates the development strategy of MSMEs in Labuan Bajo as part of a premium tourist destination in Indonesia. The study aims to formulate appropriate development strategies for MSMEs in Labuan Bajo by identifying the strengths, vulnerabilities, opportunities, and threats (SWOT) of MSMEs. The research methodology employed is descriptive analysis, which is qualitative in nature. This research conducted in-depth interviews with MSME actors and relevant stakeholders in Labuan Bajo, NTT. Several primary strategies can be developed to enhance and promote the development process of Labuan Bajo as a major priority tourist destination in Indonesia, as a result of the SWOT analysis that has been conducted. The results show that MSMEs in Labuan Bajo have great potential supported by government policies, but face challenges in market access and technology. The main strategies proposed include HR capacity building, product diversification, and marketing digitalization. The implementation of this strategy is anticipated to foster local economic development and enhance the competitiveness of MSMEs through the tourism sector.